Surface modification in the shape of a pattern using crepe paper maskant in EDM. (3rd June 2022) - Mazarbhuiya, Rashed Mustafa; Rahang, Maneswar; Saha, Subhankar
ABSTRACT: This article describes a new approach of surface modification in the shape of a pattern employing powder metallurgical (PM) green compact tool and electrical discharge machining (EDM). Patterns on the workpieces of aluminium (Al) 6061 are generated using PM green tools and crepe paper masking technique in EDM. The tool material is made of copper and tungsten powders. The pattern surface is analyzed by evaluating the output performance. The presence of electrode material in the pattern surface is identified, and the characteristics of the surface are significantly altered. The morphology and output properties of the treated material are studied, and the EDM process parameters are optimised. The deposition rate of material is found to be 15.53 mg/min where minimum roughness of 5.63 µm and minimum deviation of the edges of 15.64 µm are observed at compact load of 20 ton, peak current of 3A and pulse on-time of 200 µs.